The Rise of the Dutch Republic $1 (BVolume 08: 1563-64s - Motley, John Lothrop, 1814-1877 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Rise of the Dutch Republic $1 (BVolume 08: 1563-64" by John Lothrop Motley is a historical account written in the mid-19th century. This volume delves into the political turmoil and emerging conflicts in the Netherlands during the years 1563-64, highlighting the struggle between local nobles and the powerful Spanish monarchy. The book features key historical figures such as William of Orange, Count Egmont, and Cardinal Granvelle, as they navigate the complexities of governance, loyalty, and rebellion amid a backdrop of religious strife. The opening of this volume introduces a significant letter penned by Orange, Egmont, and Horn to King Philip II, expressing their discontent with Cardinal Granvelle's administration. Their letter paints Granvelle as a detrimental figure to the King's interests in the provinces, leading to tensions and quarrels among the Dutch nobility and the Spanish crown. As the correspondence unfolds, it becomes clear that Egmont's outspoken nature and reckless bravery create further discord within the noble ranks, while Granvelle's scheming exacerbates the underlying tensions. The political landscape is seen as precarious, with multiple factions vying for influence as they anticipate the brewing crisis that is sure to shape the future of the region. (This is an automatically generated summary.)s
Release date is 2004-01-01
This etext was produced by David Widger
Keywords: Netherlands -- History -- Eighty Years' War, 1568-1648; Netherlands -- Church history